Aedes Aegypti mosquito's breeding grounds characterization in Abreus municipality. 2016-2022 - Lisbeth Fundora Filgueiras; Jorge Enrique Rodríguez León; Esther Yarinely Hernández Dieguez; Niuvys Valera Rodríguez; Julian Sobral Rey; Idalmis Valero Valero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: knowledge about the mosquito's breeding grounds motivates residents and decision makers to work on the issues that affect the mosquito proliferation; as well as effective community participation, and success in the prevention and control of arboviral diseases. Objective: to characterize the Aedes aegypti mosquito's breeding grounds. Methods: an observational, retrospective, and cross-sectional study was carried out on Aedes aegypti's breeding grounds detected in the Abreus municipality, Cienfuegos province, from 2016 to 2022. 390 breeding grounds were the universe, for which the described variables were: statistical week, month and year of diagnosis, neighborhood, type of deposit, place of residence where it was found, and phase of the mosquito at diagnosis. Data from entomological surveys and records from the Municipal Hygiene and Epidemiology Unit's Medical Entomology laboratory were used. Results: the median number of Aedes aegypti breeding grounds corresponded to statistical week 32 of each year. The largest number of outbreaks was detected in the Abreus' neighborhood (165) and Juraguá (102); found mainly in yards (85.5 %) and low tanks (55.5 %). The larval phase in IV stage predominated (82.3 %). Conclusions: in the municipality of Abreus, the focality of Aedes aegypti mosquitoes was characterized by its highest incidence in the months of June to September, with predominance in the popular council of Abreus, especially in low tanks and yards. The largest number was diagnosed in the IV phase.